PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS IX C SMP NEGERI 1 SIMPANG KANAN KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR - Juliani '; Gimin '; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to determine the implementation of cooperative learning model STAD to increase learning motivation IPS students of class IX C SMP Negeri 1 Simpang Kanan. The number of students in this study were 23 orang.Penelitian implemented in the 2nd half of the 2015/2016 school year in February 2016.Variable measured in this study are the activities of teachers and students with the implementation of cooperative learning model STAD and motivation to learn siswa.Pengumpulan data is done using sheet observasi.Hasil this study showed that the activity of teachers in the application of cooperative learning model STAD in the first cycle, amounting to 24 to the standard classification of the degree of perfection of teachers are in a good classification. The percentage of teacher activity reached 62.50%. While in the second cycle increased with the percentage of 87.50% both categories all.The activity of the student in the first cycle with a score of 72 porsentase 52.17% on the classification of sufficiently while on the second cycle increased student activity with a score of 105 with a percentage of 76.09% good classification all.The increased student motivation in the first cycle scores obtained by students is 98 percentage 53.26% with sufficient classification. After the second cycle increased score of 143 with a percentage of 77.72% with a good classification.Based on the results of this study concluded that the implementation of cooperative learning model STAD can increase motivation to learn social science students of class IX C SMP Negeri 1 Simpang Kanan district. Rokan HilirKeywords: STAD and Motivation